Advances in Computing and Communications First International Conference, ACC 2011, Kochi, India, July 22-24, 2011, Proceedings, Part IV - Abraham, Ajith; Mauri, Jaime Lloret; Buford, John F.; Suzuki, Junichi; Thampi, Sabu M. (Springer eBooks., 2011)
This volume is the fourth part of a four-volume set (CCIS 190, CCIS 191, CCIS 192, CCIS 193), which constitutes the refereed proceedings of the First International Conference on on Computing and Communications, ACC 2011, held in Kochi, India, in July 2011. The 62 revised full papers presented in this volume were carefully reviewed and selected from a large number of submissions. The papers are the papers of the Workshop on Cloud Computing: Architecture, Algorithms and Applications (CloudComp2011), of the Workshop on Multimedia Streaming (MultiStreams2011), and of the Workshop on Trust Management in P2P Systems (IWTMP2PS2011).